SISTEM INFORMASI MENDETEKSI HAMA DAN PENYAKIT TANAMAN KOL MELALUI SISTEM PAKAR DENGAN METODE FORWARD CHAINING STUDI KASUS : BALAI PENYULUHAN PERTANIAN KECAMATAN JANGKAT: Expert System;Forward Chaining;Web;Pests and Diseases. - Rusli, Mulyadi; Sulanti, Noni (LP2M Universitas Nurdin Hamzah, 2021)
In the world of agriculture, there are many problems that prevent farmers from cultivating this group of crops, causing crop failure. The problem that is often faced is that pests and diseases become serious problems that cannot be handled properly so that plants die or do not grow properly, and result in crop failure and big losses. The purpose of the study was to build an Expert System to Detect Pests and Diseases of Cabbage Using Forward Chaining Methods at the Agricultural Extension Center, Jangkat District, a system that can replace the temporary role of experts in identifying pests and diseases of cabbage or cabbage plants accurately and quickly. An expert system for diagnosing pests and plant diseases are urgently needed to serve as a means for consultation and learning facilities for farmers, especially from Extension Centers. For this reason, the complexity and difficulties experienced by farmers or can be overcome by providing a software (expert system) in the form of an application program to determine pests and diseases that attack cabbage or cabbage plants and how to handle and prevent them appropriately. The advantage of using an expert system application using web programming is that it makes it easier for farmers to determine pests and diseases and so that there are no errors in giving conclusions about pests and diseases, which is expected to help and facilitate farmers in determining pests and diseases that attack plants.